National Agricultural Research in a Regional Context: The Small Countries of Southern Africa - Okello, Andrew E.; Eyzaguirre, Pablo B. (International Service for National Agricultural Research, 1992)
A regional approach in which a national agricultural research system can benefit from activities that take place in neighboring countries is often advocated as a way for small countr ies to overcome their size constraints. This paper reviews the regional context for agricultural research in the small countries of Southern Africa (Botswana, Lesotho, Namibia, and S waziland) from a national viewpoint. Given their limited resources, each of the the countries can benefit from increased collaboration on selected issues with other countries in the region. However, the areas of collaboration need to be selected and prioritized in relation to national needs. And levels of participation, in networks for example, need to be caref ully defined to match national capacity. Participation and collaboration in regional efforts requires that the countries themselves have well-defined research policies and priorities , that their portfolios of national research activities are aligned to capitalize on potential spillovers from the region, that the strengths of a research system characterized by in stitutional diversity are recognized, and that the different parts of the system are directed towards common policy goals. An outward-looking strategy for these small countries that builds on knowledge and technologies borrowed from the region will require a redefinition of what constitutes research- away from experimentation alone towards a broader set of funct ions. This reorientation will require new, and perhaps different, skills and qualifications from researchers and different ways of organizing and managing research activities.